The co-evolution of the genome and epigenome in colorectal cancer - Timon Heide; Jacob Househam; George D. Cresswell; Inmaculada Spiteri; Claire Lynn; Maximilian Mossner; Christopher Kimberley; Javier Fernández-Mateos; Bingjie Chen; Luís Zapata; Chela James; Iros Barozzi; et al. (2022)
Abstract Colorectal malignancies are a leading cause of cancer-related death 1 and have undergone extensive genomic study 2,3 . However, DNA mutations alone do not fully explain malignant transformation 4–7 . Here we investigate the co-evolution of the genome and epigenome of colorectal tumours at single-clone resolution using spatial multi-omic profiling of individual glands. We collected 1,370 samples from 30 primary cancers and 8 concomitant adenomas and generated 1,207 chromatin accessibility profiles, 527 whole genomes and 297 whole transcriptomes. We found positive selection for DNA mutations in chromatin modifier genes and recurrent somatic chromatin accessibility alterations, including in regulatory regions of cancer driver genes that were otherwise devoid of genetic mutations. Genome-wide alterations in accessibility for transcription factor binding involved CTCF, downregulation of interferon and increased accessibility for SOX and HOX transcription factor families, suggesting the involvement of developmental genes during tumourigenesis. Somatic chromatin accessibility alterations were heritable and distinguished adenomas from cancers. Mutational signature analysis showed that the epigenome in turn influences the accumulation of DNA mutations. This study provides a map of genetic and epigenetic tumour heterogeneity, with fundamental implications for understanding colorectal cancer biology.